A case-study to examine doctors' intentions to use IoT healthcare devices in Iraq during COVID-19 pandemic - Alhasan, Ameer; Audah, Lukman; Ibrahim, Ishaq; Al-Sharaa, Ammar; Al-Ogaili, Ali Saadon; M. Mohammed, Jabiry (Emerald Group Publishing Ltd, 2024)
Indexe by WOS